The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1995
DOI: 10.1128/mcb.15.10.5205
|View full text |Cite
|
Sign up to set email alerts
|

Ras p21Val Inhibits Myogenesis without Altering the DNA Binding or Transcriptional Activities of the Myogenic Basic Helix-Loop-Helix Factors

Abstract: Our results demonstrate that Ras p21Val inhibits terminal differentiation events by targeting the basic domain of the MRFs, and yet the mechanism underlying this inhibition does not involve altering the DNA binding or the inherent transcriptional activity of these regulatory factors. In contrast, FGF-2 and TGF-␤1 block terminal differentiation by repressing the transcriptional activity of the MRFs. We conclude that the Ras p21Val block in differentiation operates via an intracellular signaling pathway that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 57 publications
3
78
0
Order By: Relevance
“…Loss of the di erentiated phenotype is a common feature of malignant transformation. In the wellcharacterized muscle system, oncogenic H-Ras represses myogenic di erentiation by inhibiting expression of muscle-speci®c transcription factors and, at the same time, inactivating their function without altering dimerization, DNA binding or transactivating functions, with a mechanisms that is poorly understood (Kong et al, 1995). Similarly, inhibition of thyroid di erentiation upon H-Ras transformation is associated with loss of PAX-8 and TTF-2 expression, and with TTF-1 inactivation even if its DNA-binding activity and transactivating function are not a ected Missero et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of the di erentiated phenotype is a common feature of malignant transformation. In the wellcharacterized muscle system, oncogenic H-Ras represses myogenic di erentiation by inhibiting expression of muscle-speci®c transcription factors and, at the same time, inactivating their function without altering dimerization, DNA binding or transactivating functions, with a mechanisms that is poorly understood (Kong et al, 1995). Similarly, inhibition of thyroid di erentiation upon H-Ras transformation is associated with loss of PAX-8 and TTF-2 expression, and with TTF-1 inactivation even if its DNA-binding activity and transactivating function are not a ected Missero et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids pEMSV scribea2, pEM-MyoD, TnI-Luc, pGT5-Luc ((Gal4) 5 -Luc), Gal4-Elk and the pDCR vectors expressing Ras G12V and the T35S, E37G and Y40C Ras variants have been described previously (Kong et al, 1995;Ramocki et al, 1997). pSVX RasN17 expressing dominant-negative Ras was obtained from S Green (University of Iowa).…”
Section: Cell Lines and Mediamentioning
confidence: 99%
“…A number of studies also have shown that Ras activity exerts dramatic and varied e ects on developmental decisions. For example, signaling through Ras and its downstream e ectors is essential for neurite outgrowth in PC12 cells (Bar-Sagi and Feramisco, 1985;Robbins et al, 1992;Thomas et al, 1992;Wood et al, 1992), while Ras activation blocks both the biochemical and morphological di erentiation of skeletal muscle (Olson et al, 1987;Gossett et al, 1988;Konieczny et al, 1989;Lassar et al, 1989;Kong et al, 1995). The inhibition of myogenesis by oncogenic Ras has proven to be a particularly useful model for investigating the Ras e ector pathways in muscle that in¯uence individual cell growth, di erentiation and transformation functions (Ramocki et al, , 1998Weyman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which Ras inhibits myoblast differentiation, however, remains controversial. The MyoD-transactivating function has been shown to be inhibited by activated Ras in one instance (Lassar et al, 1989b) and to be unaffected in another instance (Kong et al, 1995). In addition, while myogenin has been shown to represent a crucial target of activated Ras in unestablished quail myoblasts (QMb) (Russo et al, 1997), it has recently been reported that inhibition of myogenin expression by activated Raf, a Ras effector, is not responsible for the block of myogenesis in chicken myoblasts (Johnson et al, 2002) and that MEF2A is a target of Raf-mediated inhibition in mouse myoblasts, but not in avian myogenic cells (Winter and Arnold, 2000;Johnson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%